Transracial adoption in England: a critical race and systems theory analysis. Issue 4 (2nd November 2015) - Sargent, Sarah
Abstract: The legal requirements of transracial adoption of children in England changed in 2014. An amendment to the law removed a requirement that due consideration be given to the 'child's religious persuasion, racial origin and ethnic and linguistic background'. This change was motivated by the belief that to do so would increase the number of transracial adoptions and thus decrease the number of children in care awaiting adoption. The likelihood of this change being successful is examined through a combination of critical race theory and systems theory. The combination of these theories permits an investigation into the communications between the political, legal and child welfare systems. This paper offers an enriched evaluation of the interactions of the child welfare, legal and political systems that should be of use to those who work in those systems, as well as providing a basis for understanding why this legal amendment will not achieve its objectives.